1998
DOI: 10.3109/01902149809099578
|View full text |Cite
|
Sign up to set email alerts
|

Radiological and Functional Assessment of Radiation-Induced Lung Injury in the Rat

Abstract: The purpose of this study is to develop an experimental model to measure localized radiation-induced lung injury using multiple end-points including breathing frequency, high-resolution computed tomography (CT), and radionuclide perfusion. The rats were anesthetized and the right lung irradiated with a single dose of 18 Gy using 200-kVp x-rays. The lung function of the animals was measured every 2 weeks after irradiation with the breathing rate assay. CT scanning and radionuclide lung perfusion assay were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
20
1
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 28 publications
6
20
1
2
Order By: Relevance
“…After two training sessions, a BR at rest was recorded for each rat less than a week before the irradiation and then every 2 weeks till 38 weeks postirradiation. As described earlier (22,27), an unrestrained animal was placed in a 1,500-mL air-tight but transparent tube of a whole-body plethysmograph connected to a pressure transducer. The frequency of pressure changes inside the tube was recorded and displayed on a calibrated chart as breaths per minute (bpm).…”
mentioning
confidence: 99%
“…After two training sessions, a BR at rest was recorded for each rat less than a week before the irradiation and then every 2 weeks till 38 weeks postirradiation. As described earlier (22,27), an unrestrained animal was placed in a 1,500-mL air-tight but transparent tube of a whole-body plethysmograph connected to a pressure transducer. The frequency of pressure changes inside the tube was recorded and displayed on a calibrated chart as breaths per minute (bpm).…”
mentioning
confidence: 99%
“…Less data are available concerning the use of lung CT in smaller animals, for which spatial and contrast resolution are limited. Lung CT, however, has been performed in rats for the evaluation of radiation-induced lung injury, but only lung density was considered, and radiological patterns were not precisely described [12,18,19]. In the present study, it was demonstrated that dual-helical lung CT is efficient for the detection of pulmonary sarcoid-like granulomas in the rats injected with CFA.…”
Section: Discussionmentioning
confidence: 70%
“…Measurement of the mean lung density has previously been used to study radiation induced lung injury in rats [12,18,19]. This index, however, is relatively crude and results can be influenced by many factors, including the lung area scanned and the age of the animal [22].…”
Section: Discussionmentioning
confidence: 99%
“…Next we assessed the level of known radiation-induced lung pathologies -vascular remodeling, pulmonary inflammation and fibrosis (3,6,7,9,(13)(14)(15)(16)(17)(18) -by scoring the histology of lung slides (Fig. 3).…”
Section: Relation Of Vascular Remodeling and Inflammation With Respirmentioning
confidence: 99%
“…Recently, we found that in concert with inflammation, vascular remodeling played a major role in the etiology of early RILD (7,8). It was shown that lung irradiation induced early vascular remodeling resulting in pulmonary hypertension (PH) and right ventricle (RV) hypertrophy eventually leading to cardiopulmonary dysfunction (7,9).…”
Section: Introductionmentioning
confidence: 98%